If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f(3)=-2(9)+3(3)-8
We simplify the equation to the form, which is simple to understand
f(3)=-2(9)+3(3)-8
Reorder the terms in parentheses
+(+3f)=-2*(9)+3*(3)-8
Remove unnecessary parentheses
+3f=-2+*(+9+)+3+*(+3+)-8
Reorder the terms in parentheses
+3f=+(-18)+3*(3)-8
Remove unnecessary parentheses
+3f=-18+3+*(+3+)-8
Reorder the terms in parentheses
+3f=-18+(+9)-8
Remove unnecessary parentheses
+3f=-18+9-8
We move all terms containing f to the left and all other terms to the right.
+3f=-18+9-8
We simplify left and right side of the equation.
+3f=-17
We divide both sides of the equation by 3 to get f.
f=-5.6666666666667
| W=4.66+1.66 | | W=-12+2.5y | | =12x^2-76x+595 | | 6x^2-7x-13824=0 | | X^2-4x^2-25x+100=0 | | f(x)=5x^3+3x^2-7x | | 64y^2-48ya+9a^2=0 | | 5(x-2)-3(X+4)=2(x+5) | | f(-8)=-2(-8)-12 | | x^2+48x+576=x^2+1296 | | 9=3x-6(2x+9) | | f(-4)=4(16)-5(-4) | | 49+14a+a^2=0 | | f(-1)=8(-1)+2(-1) | | f(-1)=8(0)+2(0) | | x^2+9x-322=0 | | -y+7=2-3y | | 1x-4(4-6x)=19 | | f(0)=-13(0)+5(0)-2(0)+8 | | 25y^2=1 | | 100-20m+m^2=0 | | x(30-2x)(30-2x)= | | (2x^4+3x^2+7)-(3x^4-9x^2-4x+4)= | | 0=x^5-3x^4-9x^3+25x^2-6x | | (x^2)+40x+40=4x+4 | | f(-1)=5(-1)-4(-1)+2 | | (2x^4+3x^2+7)-(3x^3+9x^2-4x+4)= | | 3x^2-2+2sinx=0 | | f(x)=x^2+8x+13 | | -20x+8+13x-15= | | 8t-10=30 | | 4.3x-3.2=x+3.6 |